Prognostic impact of serum free light chain ratio normalization in patients with multiple myeloma treated within the GMMG-MM5 trial - Klein, Eva-Maria; Tichy, Diana; Salwender, Hans; Mai, Elias K.; Duerig, Jan; Weisel, Katja; Benner, Axel; Bertsch, Uta; Akhavanpoor, Mabast; Besemer, Britta; Munder, Markus; Lindemann, Hans-Walter; et al. (Cancers, 2021)
We investigated the prognostic impact of time-dependent serum free light chain ratio (FLCr) normalization in 590 patients with secretory multiple myeloma (MM) during first-line treatment within the German-Speaking Myeloma Multicenter Group MM5 trial. Serum free light chains (sFLC) were assessed by the Freelite test at baseline, after induction, mobilization, autologous blood stem cell transplantation, consolidation and every three months during maintenance or follow up within two years after the start of maintenance. The proportion of patients with a normal or normalized FLCr increased from 3.6% at baseline to 23.2% after induction and 64.7% after consolidation. The achievement of FLCr normalization at any one time before the start of maintenance was associated with significantly prolonged progression-free survival (PFS) (p < 0.01, hazard ratio (HR) = 0.61, 95% confidence interval (95% CI) = 0.47-0.79) and overall survival (OS) (p = 0.02, HR = 0.67, 95% CI = 0.48-0.93) in multivariable time-dependent Cox regression analyses. Furthermore, reaching immune reconstitution, defined as the normalization of uninvolved immunoglobulins, before maintenance was associated with superior PFS (p = 0.04, HR = 0.77, 95% CI = 0.60-0.99) and OS (p = 0.01, HR = 0.59, 95% CI = 0.41-0.86). We conclude that FLCr normalization during therapy is an important favorable prognostic factor in MM. Therefore, we recommend serial measurements of sFLC during therapy until achieving FLCr normalization, even in patients with secretory MM.
Gesehen am 29.01.2022